Ursolic Acid Reduces the Metalloprotease/Anti-Metalloprotease Imbalance in Cerebral Ischemia and Reperfusion Injury [Corrigendum] - Wang Y; He Z; Deng S (Dove Medical Press, 2021)
Wang Y, He Z, Deng S. Drug Des Devel Ther. 2016;10:1663– 1674.   The authors have advised due to an error at the time of figure assembly, Figure 4A on page 1670 is incorrect.   The authors apologize for this error and advise it does not affect the results of the paper.   Read the original article